The gold miner's daughter : a melodramatic fairytale - Hopkins, Jackie (Peachtree Publishers, 2006)
Gracie Pearl has until sundown to find some gold to pay the rent to Mr. Bigglebottom, or he will take back the family gold mine and force her to marry him.